2018
DOI: 10.17670/mped.2018.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Contexts of School and Herder Family Communication in Mongolia: A Conceptual Framework

Abstract: Many nations around the world are engaged in pastoralism, including cattle herding among Maasai and Fulani groups in West and East African grasslands; desert camel herder groups in Arabia, North Africa, and South and Central Asia; goat and sheep herders in the Middle East; horse nomad Kazakhs in the Central Asian steppe; yak herder Tibetans in the Himalayas; and reindeer pastoralist Tungus and Chukchi groups in Northern Siberia and the Arctic Circle (Fratkin & Meir, 2005). Mongolia is one of these geographical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In Eastern and South Africa, such arrangements are often considered exploitative, with negative effects on livestock well-being and pasture health (Michler et al, 2019;Moritz et al, 2011). While we found that currently the own children are still valuable assistants in labour-intensive times for herders in the Dzungarian Gobi, maintaining the connection to their homeland (Sukhbaatar & Tarkó, 2018), we also saw a trend of the young generation leaving the herding lifestyle behind.…”
Section: Herding Traditionmentioning
confidence: 78%
“…In Eastern and South Africa, such arrangements are often considered exploitative, with negative effects on livestock well-being and pasture health (Michler et al, 2019;Moritz et al, 2011). While we found that currently the own children are still valuable assistants in labour-intensive times for herders in the Dzungarian Gobi, maintaining the connection to their homeland (Sukhbaatar & Tarkó, 2018), we also saw a trend of the young generation leaving the herding lifestyle behind.…”
Section: Herding Traditionmentioning
confidence: 78%